Correlates of Smoking During an Economic Recession Among Parents of Children with Asthma. (June 2013) - Jackson, Tracy L.; Gjelsvik, Annie; Garro, Aris; Pearlman, Deborah N.
<x xml:space="preserve">Abstract</x> Objective. We describe the correlates of smoking among parents who have a child with asthma and examine whether the correlates changed from 2008 to 2010, when the United States experienced a severe recession and a sharp increase in unemployment, a stressor that could influence smoking behavior. Methods. Data are from the 2008 and 2010 Behavioral Risk Factor Surveillance System (BRFSS), a nationally representative survey of U.S. adults age 18 and older. Separate logistic regressions estimated the association between unemployment and smoking in 2008 and 2010, adjusting for sociodemographic and other characteristics of parents of a child with asthma. Results. Being unemployed was a significant predictor of smoking in 2010 (AOR = 1.80; 95% CI: 1.24–2.61), but was not a significant predictor in 2008 (AOR = 1.26, 95% CI: 0.82–1.95). One central component of well-being, as measured by being dissatisfied with one's life, was significantly associated with parental smoking in 2010 (AOR = 2.06, 95% CI: 1.00–4.27), but not in 2008 (AOR = 1.62, 95% CI: 0.85–3.11). Several covariates had similar associations with parental smoking in both survey years, including low education, not being currently married, not having health insurance, and binge drinking. Conclusions. Our results support the idea that during hard economic times unemployment and related stressors may be strong determinants of parental smoking when a child in the home has asthma. Given that the BFRSS is a cross-sectional survey, definitive conclusions cannot be drawn regarding the causal pathway connecting unemployment, global well-being, and parental smoking.